2020
DOI: 10.11606/s1518-8787.2020054002950
|View full text |Cite
|
Sign up to set email alerts
|

Mudanças alimentares na coorte NutriNet Brasil durante a pandemia de covid-19

Abstract: OBJETIVO Descrever características da alimentação dos participantes da coorte NutriNet Brasil imediatamente antes e na vigência da pandemia de covid-19. MÉTODOS Os dados deste estudo provêm de coorte de adultos criada para investigar prospectivamente a relação entre alimentação e morbimortalidade por doenças crônicas não transmissíveis no Brasil. Para este estudo, foram selecionados os primeiros participantes (n = 10.116) que responderam por duas vezes a questionário simplificado sobre sua alimentação no dia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
70

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 7 publications
4
63
0
70
Order By: Relevance
“…Table 1 shows details of the studies, which included the FBDG from each country. Thirty-nine studies were conducted in HIC, while the other 10 studies were from LMIC [ 41 , 42 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows details of the studies, which included the FBDG from each country. Thirty-nine studies were conducted in HIC, while the other 10 studies were from LMIC [ 41 , 42 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The average sample size for the HIC studies were 12,355 ranging from 32 [ 34 ] to 25,2425 [ 30 ], while average sample size for the LMIC were 745,050 ranging from 490 [ 57 ] to 32,898 [ 51 ]. The studies were conducted in the following countries: United States of America (USA) ( n = 17) [ 27 , 32 , 34 , 35 , 46 , 48 , 49 , 50 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], Canada ( n = 6) [ 31 , 36 , 44 , 67 , 68 , 69 ], Brazil ( n = 4) [ 42 , 51 , 53 , 54 ], Switzerland ( n = 4) [ 29 , 37 , 40 , 43 ], Australia ( n = 3) [ 70 , 71 , 72 ], China ( n = 2) [ 55 , 58 ], Belgium ( n = 2) [ 38 , 73 ], Spain ( n = 2) [ 30 , 47 ], Denmark ( n = 1) [ 28 ], Egypt ( n = 1) [ 52 ], Germany ( n = 1) [ 74 ], Greenland ( ...…”
Section: Resultsmentioning
confidence: 99%
“…The Brazilian online behaviour survey ConVid, carried out from April to May 2020 with 45,161 people, registered a decrease of about 4% in regular consumption (5 days or more a week) of vegetables and beans and an increase of 4% in frozen meals, 4% in savoury snacks and 6% in chocolate/sweet biscuits/pieces of tart from 2 days or more a week (25) . In contrast, the NutriNet Brasil study, survey conducted with 10,116 individuals, showed a slight increase in the frequency of consumption of vegetables, fruits, and beans, as well as a stable high consumption of UPF during the COVID-19 pandemic (26) .…”
Section: Implications Of the Food Information Environment In The Covimentioning
confidence: 78%
“…Para os respondentes, esse resultado tem a influência do fechamento dos restaurantes no início da pandemia e o aumento do preparo de refeições nas residências. O dado encontra ressonância no estudo da NutriNet Brasil realizado em maio de 2020 com 10.116 pessoas, na qual foi observado que houve um pequeno aumento no consumo de alimentos saudáveis [33] .…”
Section: Os Canais De Comercialização Da Agricultura Familiar No Valeunclassified